Analisis Kebutuhan Flipbook Teks Tanggapan bermuatan Prinsip Kesantunan - Dwi Setiawan; Cahyo Hasanudin; Sutrimah Sutrimah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the need for a flipbook as a teaching material for response texts integrated with the principles of politeness. The background of this research stems from the limitations of response text teaching materials, which are still integrated into printed textbooks without incorporating essential politeness principles. This research employed a qualitative method with data collected through questionnaires and interviews involving seventh-grade students at two junior high schools in Dander District, Bojonegoro Regency. The findings indicate that most students prefer response text material to be presented separately and packaged in the form of an engaging and easily accessible digital flipbook. Furthermore, students consider the integration of politeness principles into response text material important to help them express opinions politely and without offending others. Therefore, it can be concluded that a flipbook teaching material integrated with politeness principles is necessary to enhance the quality of learning.